Pathways for training load variations in sub-elite youth football players - Teixeira, José Eduardo (2022)
Monitoring accumulated training load has become a research hot topic in youth football environments. However, emergent wearable and tracking tools appears to have created confusion in dose-response considerations due the availability of a high amount of data. Standardizing the classification of the load measures is vital to give meaningful in the different researches findings. Also, it is more critical than ever to turning these physiological and biomechanical data into relevant information with practical applications. Thus, this thesis aimed to: (i) review the state of the art about monitoring accumulated training and match load in football, especially in sub-elite settings; (ii) quantify the weekly training load and recovery variations performed by under-15, under17 and under-19 sub-elite football players; (iii) analyze the influence of chronological age, relative age, biological maturation status, training day, weekly microcycle and playing position on the accumulated training load and recovery status by U15, U17 and U19 sub-elite football players; (iv) examine the association between training load and recovery status in sub-elite youth football training; (iv) reduce the dimensionality of the biomechanical and physiological datasets, by a principal component approach, to describe and explain the accumulated training load pathways in youth sub-elite football training. The main conclusions of this thesis were that the accumulated training and match load variation seem to be influenced by the type of weekly schedule, player’s starting status, playing positions, age group, relative age, biological maturation status, training mode, and contextual factors. A high variation in the weekly loading distribution and a limited load variation during a competitive season. This evidence was pioneering observed in sub-elite youth training settings, reported by training load variation within age group, relative age, biological maturation, weekly microcycle, training day and playing position. Interaction effects between conditioning factors were also observed. Recovery status was positively correlated with acceleration output, as well a higher sRPE and RPE may be associated with smaller recovery state. Current thesis provides the first composite equations to assess the accumulated training load in sub-elite youth football expressed as explosiveness and impacts, high intensity running, heart bate-based measures, baseline characteristics and average running velocity.